No Jobs, Lots of Work: The Gendered Rise of the Temporary Employment Relationship in Canada, 1897-1997 - Vosko, Leah F. (York University, 1998)
This dissertation examines the history and evolution of the employment relationship associated with the contemporary temporary help industry in Canada from the late nineteenth to the late twentieth century. Using gender as a central lens of analysis, it explores how, and to what extent, this employment relationship is becoming a nom for a more diverse group of workers in the Canadian labour market. In so doing, the dissertation develops the following argument: with the shift away from the standard employment relationship since the early 1970s and the coincident nse of the temporary employment relationship – two developments indicative of the ferninization of employment – workers situated at the expanding margins of the labour market are increasingly treated like commodities. A growing body of scholarship argues that the nature of employment is changing, citing the spread of non-standard forms of employment and women's rising and/or consistently high labour force participation rates as evidence of this claim. This dissertation confirms that important changes are indeed taking place in the labour market but it argues that the tenor and direction of these changes oniy corne into Full view when they are examined in light of continuity as well as change. To this end, it probes the shape of dualism in the Canadian labour market historically, paying particularly attention to its gendered and racialized character, through a case study of the temporary employment relationship. The dissertation begins by providing a conceptual map for understanding and interpreting contemporary employment trends that engages in three broader theoretical inquiries: the investigation of labour power's peculiar commodity statu under capitalism; the exploration of the rise and decline of the standard employment relationship as a normative mode1 of employment; and the examination of the gendered character of prevailing employment trends. Following this overview, the body of the dissertation traces the history of the temporary employment relationship in Canada, examining how its three core actors – the temporary heip agency, the customer and the worker – have adapted to shifting employment trends and gendered employment noms and negotiated developments at the regdatory level over the course of the twentieth century. In probing the evolution of the temporary employment relationship, it devotes special emphasis to examining the role and fùnction of early precursors to the modem temporary help agency (e-g., private employment agents such as general labour agents and so-called padrones), its immediate forerunners (Le., the 'classic' temporary help agency of the 1950s) and its most recent manifestation (Le., the employment and staffing service). AIthough the dissertation focuses on the Canadian context, it also traces developments at the international and supra-national level throughout the twentieth century, developrnents that have often mirrored, frequently affected, and occasionally even prefigured trends in Canada. Interdisciplinary in its focus, the dissertation approaches the evolution of the temporary employment relationship from a range of angles, building on scholarship fiom the fields of Law, History, Political Econorny, Sociology and Industriai Relations. The research methodoIogies used include: archivaVhistorica1 research; field observation; interviews with temporary help workers, agency managers and customers as well as government officials, representatives from organized labour and industry leaders; and analysis of industry, government and legal documentation at the municipal, provincial, national and supra-national levels.
OCLC: 1306069848
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques; dissertations